An overview of biosimilars approvals by thirteen regulatory authorities: A cross national comparison - Lacerda da Silva Machado, Fernanda (2023)
Biosimilars are biological medicines highly similar to a previously licensed reference product and their licensing is expected to improve access to biological therapies. This study aims to present an overview of biosimilars approval by thirteen regulatory authorities (RA). The study is a cross-national comparison of regulatory decisions involving biosimilars in Argentina, Australia, Brazil, Chile, Canada, Colombia, Europe, Hungary, Guatemala, Italy, Mexico, Peru and United States. We examined publicly available documents containing information regarding the approval of biosimilars and investigated the publication of public assessment reports for registration applications, guidelines for biosimilars licensing, and products approved. Data extraction was conducted by a network of researchers and regulatory experts. All the RA had issued guidance documents establishing the requirements for the licensing of biosimilars. However, only three RA had published public assessment reports for registration applications. In total, the investigated jurisdictions had from 19 to 78 biosimilars approved, most of them licensed from 2018 to 2020. In spite of the advance in the number of products in recent years, some challenges still persist. Limited access to information regarding the assessment of biosimilars by RA can affect confidence, which may ultimately impact adoption of these products in practice.